Exploring EFL Pre-service Teachers' Experiences in Accessing Information to Develop Digital Storytelling as Learning Media: A Narrative Inquiry - Drajati, Nur Arifah; Ekawati, Febriani Fajar; Ramli, Murni; Rochsantiningsih, Dewi; Haryati, Sri; Aniq, Lailatun Nurul (Lembaga Bale Literasi, 2024)
Technology's darting advancement made digital literacy a key component in pre-service teacher professional development. Their digital literacy ability is reflected in their teaching, including designing learning media such as digital story-telling. Hence, this study is designed to understand how EFL pre-service teachers access information as a part of digital literacy to create digital storytelling learning media. The data were gathered from 28 students of the English Education Department in the Cross-Cultural Understanding course by having them write diaries to reflect on their experiences in designing digital storytelling learning media. Using a narrative inquiry method, the data were analyzed through three steps: repeatedly reading, coding, and categorizing it into thematic headings. The findings from data analysis indicate the mastery of various dimensions of digital literacy, namely photo-visual, reproductive, branching, informational, and social-emotional literacy, by EFL pre-service teachers, substantially contributed to the quality of teaching and student engagement in digital-based learning. This research underscores the need to integrate digital literacy training into teacher education programs to better prepare future educators for the demands of modern, technology-driven classrooms.